A selective glucose sensor: the cooperative effect of monoboronic acid-modified poly(amidoamine) dendrimers. Issue 36 (18th April 2018) - Tsai, Ching-Hua; Tang, Yi-Hsuan; Chen, Hui-Ting; Yao, Yi-Wen; Chien, Tun-Cheng; Kao, Chai-Lin
Abstract : For the first time, monoboronic acid derivatives exhibited selective binding to glucose over other saccharides. Abstract : Selective glucose binding was identified through five generations of monoboronic acid-functionalized PAMAM dendrimers. The best selectivity obtained when using G3 dendrimers (1b ) generated 71.1, 94.9, and 1309 times stronger binding than when using galactose, fructose, and lactose, respectively. Further experiments using dendrimer analogues and glucose derivatives suggested that two nearby monoboronic acids cooperatively bound one glucose.